2020
DOI: 10.3389/fneur.2020.01041
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Gastrointestinal Microbiome Composition in PD: A Pivotal Role of Covariates

Abstract: Altered gut microbiota may trigger or accelerate alpha-synuclein aggregation in the enteric nervous system in Parkinson's disease (PD). While several previous studies observed gut microbiota alterations in PD, findings like diversity indices, and altered bacterial taxa itself show a considerable heterogeneity across studies. We recruited 179 participants, of whom 101 fulfilled stringent inclusion criteria. Subsequently, the composition of the gut microbiota in 71 PD patients and 30 healthy controls was analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 66 publications
2
44
0
Order By: Relevance
“…Beta diversity emphasizes the similarity of intestinal microflora structure of different persons ( Table 2). According to the current research data, the beta diversity of PD patients is significantly different from that of healthy people, and in longitudinal follow-up, the difference of beta diversity of intestinal microflora of PD patients becomes more obvious (Barichella et al, 2019;Cosma-Grigorov et al, 2020). The diversity of intestinal microorganisms in human body reflects the regulation of metabolism and immune system.…”
Section: Clinical Study Of Intestinal Flora In Patients With Pdmentioning
confidence: 93%
See 3 more Smart Citations
“…Beta diversity emphasizes the similarity of intestinal microflora structure of different persons ( Table 2). According to the current research data, the beta diversity of PD patients is significantly different from that of healthy people, and in longitudinal follow-up, the difference of beta diversity of intestinal microflora of PD patients becomes more obvious (Barichella et al, 2019;Cosma-Grigorov et al, 2020). The diversity of intestinal microorganisms in human body reflects the regulation of metabolism and immune system.…”
Section: Clinical Study Of Intestinal Flora In Patients With Pdmentioning
confidence: 93%
“…In a study investigating the functional implications of microbial and viral gut metagenome changes in PD patients in the early stage without the use of L-dopa (Bedarf et al, 2017), it was found that various combinations of anti-PD drugs (mainly dopamine agonists, monoamine oxidase inhibitors, and amantadine) had no significant effect on the intestinal bacteria in PD patients. Heintz bushart et al analyzed PD patients taking levodopa and found that levodopa was an important covariate affecting the abundance of intestinal flora and duration of disease, but without affecting intestinal Enterobacteriaceae (Cosma-Grigorov et al, 2020). In order to evaluate the effect of antiparkinsonian drugs on microbial composition, Zhang et al analyzed the relationship between four antiparkinsonian drugs (levodopa, dopamine agonist, anticholinergic drug, and amantadine) and the intestinal microflora of PD patients.…”
Section: Family Genusmentioning
confidence: 99%
See 2 more Smart Citations
“…PSM reduced the influence of lifestyle variables which might attenuate the relevance between fecal bacteria and the risk of gastric cancer [ 48 ]. PSM was also used to control the effect of clinical variables on microbiota composition to find the relationship between fecal microbiota and Parkinson’s disease [ 49 ].…”
Section: Methodsmentioning
confidence: 99%